A review on environmental research - Oke, Sunday Ayoola (Journal of Environmental Engineering and Landscape Management, 2004)
Environmental research has recently attracted much attention in the scientific and engineering communities. The resounding theme in the literature is an emphasis on achieving a globally friendly environment while the environment is preserved and its quality improved upon. Attaining a high level of health status has also been the primary concern of its stakeholders. New technologies are continuing to emerge, thereby stimulating mutual research interaction among the scientific and technical communities on all the six continents. The inter‐disciplinary problems posed by natural and human‐induced changes in the earth's environment has therefore been the concern of many investigators in ecology, geography, civil engineering, marine engineering, biology, chemistry, earth science and physics, among others. Yet, there is a gap in the body of knowledge on environmental research. The popular and scholarly literature is deficient in studies that reflect the past, present and future trends of research in the field. This paper provides a comprehensive review of the field. The review covers general surveys, models, empirical studies and cases of original research in the field. Studies considered are those that have contributed significantly to knowledge. The review raises a new challenge and predicts growth areas in the next several decades.Aplinkosauginių tyrimų apžvalgaSantrauka. Pastaruoju metu aplinkosauginiais tyrimais domisi mokslininkai ir inžinieriai. Literatūroje akcentuojama, kad pasaulyje aplinka turi būti saugoma globaliai bei gerinama jos kokybė. Tai įgyvendinti padeda aukšto lygio laimėjimai medicinoje, plėtojamos naujos technologijos, skatinančios mokslinius techninius tyrimus šešiuose pasaulio kontinentuose. Tarptautinė problema, kurią sukėlė neteisėta žmogaus veikla aplinkoje, sprendžiama atliekant įvairius ekologinius, geografinius, aplinkos ir jūrų inžinerijos, biologinius, cheminius, geologinius, fizikinius ir kt. tyrimus. Atliekant mokslinius tyrimus nepakanka populiarios bei akademinės literatūros, atspindinčios praeitį, dabartį ar prognozuojančios ateitį. Šiame straipsnyje nagrinėjami aplinkosauginiai tyrimai, pateikiama bendroji situacija aprašoma modeliai, empirinės studijos bei originalių tyrimų pavyzdžiai. Apžvelgti tyrimai bus reikšmingi plėtojant šią tematiką ir ateityje. Keliami klausimai bei numanomi atsakymai į juos bus aktualūs dar keletą dešimtmečių.Reikšminiai žodžiai: aplinkos apsauga, apžvalga, aplinkos mokslai, aplinkos inžinerija, teršalai, užterštumas.First Published Online: 14 Oct 2010